Microbiota–immune dysregulation in cervical cancer patients from Western Mexico: linking gut dysbiosis and NK cell exhaustion as promising biomarkers - Klimov-Kravtchenko, Ksenia; Baltazar-Díaz, Tonatiuh Abimael; Haramati, Jesse; Castaño-Jiménez, Paula Alejandra; Solorzano-Ibarra, Fabiola; Rojas-Diaz, Jose Manuel; Garcia-Barrientos, Nadia Tatiana; Cruz-Ramos, Jose Alfonso; Facundo-Medina, Carmen Gahia; Del Toro-Arreola, Susana; Bueno-Topete, Miriam Ruth (Frontiers in Immunology, 2025)
Alterations in gut microbiota composition have been implicated in various diseases, including cancer. Recent evidence suggests that intestinal microbiota may influence the efficacy of immunotherapy. In this study, we investigated the relationship between gut dysbiosis and NK cell exhaustion in Mexican patients with cervical cancer (CC), a connection not previously explored. This cross-sectional study included newly diagnosed CC patients, a separate cohort of post-radio-chemotherapy (RCT) patients, and healthy donors (HD). Fecal microbiota profiles were assessed using 16S rRNA sequencing, while peripheral NK cell immune checkpoint expression was analyzed by multiparametric flow cytometry. CC patients exhibited significant gut dysbiosis, marked by reduced α-diversity, enrichment of pro-inflammatory taxa (Escherichia-Shigella, Prevotella), depletion of short-chain fatty acid (SCFA)-producing bacteria (Ruminococcus, Christensenellaceae), and enrichment of microbial metabolic pathways related to inflammation, oxidative stress, nutrient limitation, and immune suppression. Dysbiosis was more pronounced in patients after RCT, with further enrichment of Phascolarctobacterium. In parallel, NK cells displayed a putative exhausted phenotype, with elevated expression and co-expression of PD-1, LAG-3, TIM-3, TIGIT, BTLA, and NKG2A. A dysbiosis score and an NK exhaustion score were developed, revealing a significant positive correlation between microbial imbalance and NK cell exhaustion. Machine learning analysis identified the Escherichia/Ruminococcus ratio and PD-1+CD56bright NK cells as predictive markers of CC. Moreover, both dysbiosis and NK cell exhaustion markers were significantly associated with reduced patient survival. This is the first study to demonstrate a link between gut microbiota alterations and NK cell exhaustion in CC. Our findings suggest that gut dysbiosis may contribute to impaired anti-tumor immunity. This study supports the rationale for microbiota-targeted interventions as adjunctive strategies in CC, although prospective validation is required.